Retrospective benefit-cost analysis of bovine brucellosis control in the state of Mato Grosso, Brazil: 2003 to 2014 - Barros, Marcelo Luís (2022)
From 2001, due to the launching of the National Program for the Control and Eradication of Brucellosis and Tuberculosis, Brazil began a series of studies aimed at the epidemiological characterization of bovine brucellosis in its federative units. In the state of Mato Grosso, studies conducted in 2003 and 2014 verified a reduction in the prevalence of infected herds from 41.2% (38.0; 44.4) to 24% (21.3; 26.8) and in the prevalence of animals from 10.2% (7.4; 13.1) to 5.1% (3.5; 7.2). These results stemmed from the efficient calf vaccination program with S19 implemented by the state. From this scenario, the present study quantified and compared the benefits and costs of bovine brucellosis control in the state through an accounting analysis. When considering private and public costs, the NPV was estimated at US$ 37.5 million, the IRR was calculated at 31%, and the BCR was 2.3. When considering only the private costs, the NPV was US$ 51.3 million, the IRR was 46% and the BCR was 3.43, indicating that the cattle producer in Mato Grosso had a return of US$ 3.43 for each US$ 1.00 invested. Therefore, the bovine brucellosis control actions carried out in the state of Mato Grosso between 2003 and 2014 were highly advantageous from the economic point of view. However, since bovine brucellosis is an important anthropozoonosis, the economic advantages resulting from its combat should be seen only as a bonus, since there is no need of economic justification for the implementation of risk mitigation measures.